Shembe religion's integration of African traditional religion and Christianity : a sociological case study - Shange, Nombulelo Tholithemba (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
The Shembe Church's integration of African Traditional Religion and Christianity has been met by many challenges. This merger has been rejected by both African traditionalists and Christians. The Shembe Church has been met by intolerance even though the movement in some ways creates multiculturalism between different people and cultures. This thesis documents the Shembe Church's ideas and practices; it discusses how the Shembe Church combines two ideologies that appear to be at odds with each other. In looking at Shembe ideas and practices, the thesis discusses African religion-inspired rituals like ukusina, ancestral honouring, animal sacrificing and virgin testing. The thesis also discusses the heavy Christian influence within the Shembe Church; this is done by looking at the Shembe Church's use of The Bible and Moses' Laws which play a crucial role in the Church. The challenges the Shembe Church faces are another main theme of the thesis. The thesis looks at cases of intolerance and human rights violations experienced by Shembe members. This is done in part by looking at the living conditions at eBuhleni, located at Inanda, KZN. The thesis also analyses individual Shembe member's experiences and discusses how some members of the Shembe church experience the acceptance of the Shembe religion in South African society. This thesis concludes by trying to make a distinction between intolerance and controversy. I try to highlight the idea that what many Shembe followers see as discrimination and intolerance towards them is sometimes a difference in opinion from other cultural groups. Sometimes these differences are not geared towards criticising other religious groups or perpetuating intolerance.
Keywords: Shembe Church; Christianity and other religions -- South Africa -- Inanda; Christianity and culture -- South Africa -- Inanda; Independent churches -- South Africa -- Inanda; Religious tolerance -- South Africa -- Inanda; South Africa -- Religious life and customs